E-WOM dan Influencer Endorsement: Pengaruhnya terhadap Minat Beli Produk Travel Umrah dimediasi oleh Brand trust (Studi pada Niat Umroh Tour & Travel Bogor) - Muhamad Komarudin; Destiana Kumala; Sawqi Saad El Hasan (Universitas Syiah Kuala, 2025)
In the competitive landscape of digital-era religious tourism, this study explores the influence of Electronic Word of Mouth (E-WOM) and influencer endorsement on purchase intention for Umrah travel services, with brand trust as a mediating variable. Using a quantitative, causality-based research design and SmartPLS 4 for data analysis, this study collected responses from 123 consumers of Niat Umroh Tour Travel. The results revealed that EWOM significantly impacts both brand trust and purchase intention, emphasizing the power of authentic consumer reviews in decision-making. Conversely, influencer endorsement positively affects brand trust but lacks a direct or mediated influence on purchase intention. Furthermore, brand trust was found to partially mediate the relationship between E-WOM and purchase intention, albeit not significantly. These findings highlight that consumer-generated content plays a more dominant role than influencer promotion in building trust and encouraging purchases in the context of religious travel. The study provides theoretical insights into the application of the S-O-R model and offers practical implications for optimizing digital marketing strategies through trusted consumer engagement.